Issues for Effective Distance Learning: a Challenge in Online Education - Quesada Pacheco, Allen (2009)
Online distance learning promotes the opportunity to meet the needs of students who are unable to attend on-campus classes. There are many distance learning benefits: increased access to learning, enhancement of life-long learning, ability to do interactive teamwork between groups, access to experts worldwide and to a tremendous volume of online databases, the use of higher order thinking strategies by the learners, and the development of self-directed, autonomous learners. However, the success of online distant learning will depend on the demanding roles for both teachers and students, and an adequate, effective, and strategic use of the synchronous and asynchronous modes of communication.